Sistem Informasi Manajemen Logistik dan Peralatan Studi Kasus: BPBD Kabupaten Wonogiri - Anisa Pamiliawati; Nanang Maulana Yoeseph; Ovide Decroly Wisnu Ardhi; Sahirul Alim Tri Bawono; muhammad Asri Safi'ie (IJAI (Indonesian Journal of Applied Informatics), 2020)
Almost all sub-districts in Wonogiri Regency have the potential to be vulnerable to natural disasters ranging from landslides, fires, floods, whirlwinds, moving land, sinking land, and drought. Losses arising from the disaster in the form of damaged homes and fatalities. Warehouse management aims to ensure the availability of logistical support and equipment at all times. An information system is created to monitor expiration dates, calculate aid allocations, and document movement of goods to calculate stock. Food logistics is prone to expiration, so it must be monitored so that it is in good condition for assistance. Calculating the allocation of aid is done to find out the number of days needed to make further distribution adjustments. The allocation calculation uses the fair share allocation method. The results achieved are managing category data, source of procurement data, sub-district data, village data, disaster data, item data, inventory data, expired data, incoming goods data, detail data of incoming goods, improper goods data, post data, calculated data, outgoing goods data, detail data of outgoing goods, and borrowing data.